[tex]1)f:\mathbb{R}\rightarrow\mathbb{R} \: \: ,f(x)=2x [/tex]
[tex]f \: impara < = > f( - x) = - f(x)[/tex]
[tex]f( - x) = 2 \times ( - x) = - 2x[/tex]
[tex] - f(x) = - (2x) = - 2x[/tex]
[tex] = > f \: impara[/tex]
[tex]2)f:\mathbb{R}\rightarrow\mathbb{R} \: \: ,f(x)=x + 1[/tex]
[tex]f \: para < = > f( - x) = f(x)[/tex]
[tex]f( - x) = - x + 1[/tex]
[tex]f(x) = x + 1[/tex]
[tex]f( - x) \neq f(x) = > f \: nu \: este \: para[/tex]
[tex]f \: impara < = > f( - x) = - f(x)[/tex]
[tex]f( - x) = - x + 1[/tex]
[tex] - f(x) = - (x + 1) = - x - 1[/tex]
[tex]f( - x) \neq - f(x) = > f \: nu \: este \: impara[/tex]